Evaluación del extracto de licopeno partiendo de residuos de diferentes frutas y hortalizas, aplicado en un producto cosmético (2019)
The purpose of this research is to evaluate the lycopene extract obtained from the residues of different fruits and vegetables, for use in a cosmetic product. In general terms in the cosmetic industry dyes are widely used to generate products with a great diversity of shades; however, many of these contain substances that can generate health effects for their consumers; In this way it is necessary to resort to the use of natural dyes, which can meet the objective desired by the industry without causing damage to the customer. One of these compounds is Lycopene, which in addition to providing red tones, also has nutraceutical and bactericidal properties, which make this compound a great alternative for use in the cosmetic industry and many other industries such as food. Taking this into account, through the development of this project, it is intended to carry out the extraction of lycopene from the waste generated in various market places, both wholesale and retail; which are not suitable for human consumption, but are still usable as raw materials for obtaining natural dyes (lycopene).